An electrochemical synthesis of a rare-earth(La3+)-doped ZIF-8 hydroxyapatite composite coating for a Ti/TiO2 implant material. (26th March 2021) - Zhang, Ziqi; Ni, Xiang; Yao, Kaida; Zhang, Siqi; Liu, Yang; Sun, Yueqiu; Wang, Xiangzhi; Huang, Weimin; Zhang, Yan
Abstract : Enhance the antibacterial and anti-corrosion property on the premise of minimizing the biocompatibility loss of titanium implants. Abstract : Titanium has been applied to implants over the last decades due to its excellent biocompatibility and mechanical properties. However, there are still some drawbacks for titanium and its alloys to overcome. Thus, in this study, a novel electrochemical synthesis process has been developed to fabricate TiO2 nanotube array, hydroxyapatite and rare-earth (La 3+ ) doped ZIF-8 nanoparticle composite coating, which can enhance the antibacterial and anti-corrosion property on the premise of minimizing the biocompatibility loss of titanium implants. Compared with traditional processing methods, electrochemical machining is more time-saving, energy-saving and environment-friendly. Thus, it provides an alternative way to produce medical implants.